PELAKSANAAN OTONOMI SEKOLAH DI DALAM UPAYA PENYELENGGARAAN PENDIDIKAN YANG EFEKTIF - Anastasia Dewi Anggraeni (Faktor Jurnal Ilmiah Kependidikan, 2016)
Abstract: School autonomy is a concept that offers policy management for decision-makingto the school in an effort involving the entire school in an effort to provide education that iseffective. This study aims to investigate the implementation of school autonomy in theimplementation of effective education. The method used is descriptive qualitative method.The results showed that: Schools prepare annual work plans and work plan of four years bydeveloping the field of curriculum and learning, student affairs, energy, infrastructure, finance,community and special services; While the school evaluation includes, supervision, evaluationof learning, school self-evaluation and accreditation of schools; Supporting factors, numberand adequate teacher competence, commitment to the school community, the division of tasksaccording to the teacher the ability of teachers, inadequate school facilities and infrastructure.Keywords: School Autonomy, the Implementation of Effective Education